2003
DOI: 10.1103/physrevb.67.174515
|View full text |Cite
|
Sign up to set email alerts
|

Short-wavelength cutoff effects in the ac fluctuation conductivity of superconductors

Abstract: The short wavelength cutoff has been introduced in the calculation of ac fluctuation conductivity of superconductors. It is shown that a finite cutoff leads to a breakdown of the scaling property in frequency and temperature. Also, it increases the phase φ of the complex conductivity (tan φ = σ2/σ1) beyond π/4 at Tc. Detailed expressions containing all essential parameters are derived for 3D isotropic and anisotropic fluctuation conductivity. In the 2D case we obtain individual expressions for the fluctuation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…The analytical result of the integration in Eq. (1) and its application in the data analysis has been reported in detail 23 . A careful analysis has shown that, due to this cutoff, the real and imaginary parts of the ac fluctuation conductivity are not equal at T c .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…The analytical result of the integration in Eq. (1) and its application in the data analysis has been reported in detail 23 . A careful analysis has shown that, due to this cutoff, the real and imaginary parts of the ac fluctuation conductivity are not equal at T c .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Note that we have used here the thermodynamically correct form k B T , rather than the approximative k B T c used before 23 . The latter will be used below only in theoretical simulations where ξ(T )/ξ 0 is used as the only variable.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations